2016
DOI: 10.1186/s13395-016-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein β is required for satellite cell self-renewal

Abstract: BackgroundPostnatal growth and repair of skeletal muscle relies upon a population of quiescent muscle precursor cells, called satellite cells that can be activated to proliferate and differentiate into new myofibers, as well as self-renew to replenish the satellite cell population. The balance between differentiation and self-renewal is critical to maintain muscle tissue homeostasis, and alterations in this equilibrium can lead to chronic muscle degeneration. The transcription factor CCAAT/enhancer binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Therefore, these results indicate that Notch1 and Notch2 are crucial for maintaining the proliferative state of satellite cell‐derived myoblasts, although Notch3 may have the opposite function, acting as a repressor of satellite cell‐population expansion . A recent study reported that C/EBPβ, a transcription factor CCAAT/enhancer binding protein β, acts as a direct positive regulator for Notch2 expression but not for Notch1 and Notch3 , controlling satellite‐cell self‐renewal during muscle regeneration . Interestingly, Bi et al have reported stage specific roles of Notch1 during myogenesis .…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, these results indicate that Notch1 and Notch2 are crucial for maintaining the proliferative state of satellite cell‐derived myoblasts, although Notch3 may have the opposite function, acting as a repressor of satellite cell‐population expansion . A recent study reported that C/EBPβ, a transcription factor CCAAT/enhancer binding protein β, acts as a direct positive regulator for Notch2 expression but not for Notch1 and Notch3 , controlling satellite‐cell self‐renewal during muscle regeneration . Interestingly, Bi et al have reported stage specific roles of Notch1 during myogenesis .…”
Section: Discussionmentioning
confidence: 92%
“…In vivo , loss of C/EBPβ in satellite cells results in larger myofibers and enhanced regenerative capacity after a single injury 22 . However, in this model, muscle regeneration was defective after a second injury due to impaired self-renewal and a reduction in the satellite cell pool supporting repair 23 . Although the role of C/EBPβ in satellite cell function has been elucidated, the specific mechanism by which C/EBPβ inhibits myogenic differentiation remains unknown.…”
Section: Introductionmentioning
confidence: 81%
“…The expression of C/EBPβ was also positively modulated in SOL muscles of HFD rats. However, the increased C/EBPβ expression in leukocyte-derived RNA samples were previously associated with increased muscle strength in humans ( Harries et al, 2012 ) and enhanced satellite self-renewal leading to muscle regeneration in mice ( Lala-Tabbert et al, 2016 ). Conversely, C/EBPβ is also involved in the process through which pre-adipocytes are differentiated toward a mature adipocyte phenotype ( Tanaka et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%